Em nome da democracia: a intervenção branca dos EUA na Venezuela chavista - Salgado, Tiago Santos (2019)
The present study aims to analyze how the US intervened in Venezuela between 2004 and 2009, bearing in mind the major importance of that country in the US interests and influence. For this analysis, the set of documents we used was a series of secret documents produced by US embassies in Caracas and other Latin American countries which discusses a correlation of Venezuelan social and political, as well as a strategy of the US diplomatic corps to intervene in civil society and in the organization of the Venezuelan opposition in an attempt to destabilize the Chávez government, which adopted policies that were understood as old to target American companies in Venezuela. All of these documents are available in the Wikileaks website